Rare case of a conjunctival cyst formation in an anophthalmic socket of a 10 years old patient - Mohamed Abdallahi Ould Hamed; Imane Tarib; Fouad Elasri (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2018)
Evisceration is a widely performed surgery in the pediatric population, the most common etiology for children is trauma and malignant retinal tumors. The procedure is safe and the complications are rare and often easily manageable.  We report the case of a 10 years old male patient, who had undergone evisceration surgery of the right eye 2 years before his admission, following a penetrating ocular trauma. The trauma circumstances were reported as accidental knife perforation. The patient was hospitalized and beneficiated from sutures of the globe injuries, associated to parenteral and local fortified antibiotics treatments. The follow-up was marked by installation of chronic painful endophthalmitis that was managed with an evisceration and hydroxyapatite implant. Two years later, the ophthalmic examination revealed the presence of 2 conjunctival cysts underneath the prosthesis, with no exteriorization of the hydroxyapatite implant. A surgery was then performed with removal of the conjunctival cysts.